2002
DOI: 10.1188/02.onf.481-491
|View full text |Cite
|
Sign up to set email alerts
|

Year 2000 Oncology Nursing Society Research Priorities Survey

Abstract: ONS Research Priority Survey results provide an important foundation for developing future research across the entire scope of oncology nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Many patients face uncertainty, and many have to undergo unpleasant and often-debilitating treatments [12,43]. Subsequently, symptom management and self-care remains a high priority for both patients and health professionals [48]. Recent changes to the structure of cancer services in the UK have seen an emphasis on the utilisation of community and out-patient-based services for treatment administration and aftercare [12, 38,50].…”
Section: Introductionmentioning
confidence: 99%
“…Many patients face uncertainty, and many have to undergo unpleasant and often-debilitating treatments [12,43]. Subsequently, symptom management and self-care remains a high priority for both patients and health professionals [48]. Recent changes to the structure of cancer services in the UK have seen an emphasis on the utilisation of community and out-patient-based services for treatment administration and aftercare [12, 38,50].…”
Section: Introductionmentioning
confidence: 99%
“…Ropka et al found in the Year 2000 ONS Research Priorities Survey that quality of life ranked second among the top 20 research priorities of sampled nurses [1]. Other priorities included neutropenia/immunosuppression (fifth), as well as depression and stress-coping adaptation in thirteenth and fourteenth place respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1 Managing cancer symptoms and QoL issues are high priorities for oncology clinicians. 2 Furthermore, attending to symptoms and side effects of treatment promotes safe and effective delivery of cancer therapies and may prevent or reduce the use of emergency department (ED) services and unplanned hospital admissions (HAs).…”
mentioning
confidence: 99%